2021
DOI: 10.1002/adhm.202100053
|View full text |Cite
|
Sign up to set email alerts
|

Mg Biodegradation Mechanism Deduced from the Local Surface Environment under Simulated Physiological Conditions

Abstract: Although certified magnesium-based implants are launched some years ago, the not well-defined Mg degradation mechanism under physiological conditions makes it difficult to standardize its use as a degradable biomaterial for a wide range of implant applications. Among other variables influencing the Mg degradation mechanism, monitoring the pH in the corrosive solution and, especially, at the corroding interface is important due to its direct relation with the formation and stability of the degradation products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…These include metal ion release, 14 adsorption of inorganic species (Ca 2+ , HPO 4 2– , H 2 PO 4 – , and HCO 3 – ), 15 , 16 and formation of complex corrosion products. 17 , 18 Mg and Mg alloys are promising materials for either macro- or miniscale medical devices 19 , 20 because they have superior biocompatibility 21 and bioresorbability or biodegradability, 22 , 23 alongside appropriate mechanical properties. 24 Nevertheless, these metals interact with protein molecules and require special attention when considering their corrosion and biodegradation behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include metal ion release, 14 adsorption of inorganic species (Ca 2+ , HPO 4 2– , H 2 PO 4 – , and HCO 3 – ), 15 , 16 and formation of complex corrosion products. 17 , 18 Mg and Mg alloys are promising materials for either macro- or miniscale medical devices 19 , 20 because they have superior biocompatibility 21 and bioresorbability or biodegradability, 22 , 23 alongside appropriate mechanical properties. 24 Nevertheless, these metals interact with protein molecules and require special attention when considering their corrosion and biodegradation behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption of proteins onto Mg and its alloys is a complicated process because multichemical and electrochemical processes occur simultaneously. These include metal ion release, adsorption of inorganic species (Ca 2+ , HPO 4 2– , H 2 PO 4 – , and HCO 3 – ), , and formation of complex corrosion products. , Mg and Mg alloys are promising materials for either macro- or miniscale medical devices , because they have superior biocompatibility and bioresorbability or biodegradability, , alongside appropriate mechanical properties . Nevertheless, these metals interact with protein molecules and require special attention when considering their corrosion and biodegradation behavior. , It is reported that depending on their type, proteins can inhibit or accelerate (detrimental impact) Mg degradation processes .…”
Section: Introductionmentioning
confidence: 99%
“…[ 59 , 64 , 65 ]. These compounds with low solubility product constant (K sp ) precipitate as insoluble in the corrosion layer [ 66 , 67 , 68 , 69 ], which is beneficial for slowing the corrosion rate [ 59 , 70 ] and stabilizing the local pH [ 55 , 56 , 71 ]. However, in this process, the hydroxide film can gradually become unstable [ 72 ], facilitating the penetration of Cl − ions in this quasi-protective film [ 73 , 74 , 75 ].…”
Section: Corrosion Behaviormentioning
confidence: 99%
“…Multiple reports refer to a strong corrosion inhibition effect when Ca 2+ is combined with anions that form sparingly soluble precipitates in an alkaline environment, which is immediately (within the first minute of immersion) generated on Mg interface upon contact with aqueous electrolytes. These ions include phosphates (H 2 PO 4 − /HPO 4 2− /PO 4 3− ), carbonates (HCO 3 − and CO 3 2− ), and fluorides, F − [ 24 , 25 , 50 , 55 , 56 ]. Under the presence of Ca 2+ cations, the precipitation of several Ca-containing phases such as hydroxyapatite (Ca 5 (PO 4 ) 3 OH), CaMg(CO 3 ) 2 , and CaCO 3 occurs on magnesium surface, prompted by the alkalinization front due to cathodic HER and ORR.…”
Section: Inorganic Inhibitorsmentioning
confidence: 99%